Implementasi Manajemen Strategik Berbasis Balanced Scorecard dalam Meningkatkan Mutu Pelayanan di Klinik Utama Glaria Bandung - Yanuar Ermawati; Tia Oktavia; Yuan Ade Sukma; Purwadhi; Yani Restiani Widjaja (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the implementation of the Balanced Scorecard (BSC) as a strategic performance management tool at Klinik Utama Glaria Bandung. The clinic faces challenges in improving service quality, which not only focuses on financial aspects but also includes customer perspectives, internal business processes, and employee learning and growth. Therefore, the implementation of BSC is expected to provide a solution for aligning these dimensions to enhance the clinic's overall performance and achieve strategic goals. The research method used in this study is descriptive qualitative, with data collection techniques including in-depth interviews with five key informants consisting of leaders, medical staff, administrative staff, and patients. These interviews aim to explore their understanding of the BSC implementation and its impact on the clinic's performance. Additionally, data were also obtained through observation and documentation related to BSC implementation at the clinic. The results show that the application of the BSC has had a positive impact on improving operational efficiency, patient satisfaction, and interdepartmental coordination. The implementation of the BSC has also helped create a more adaptive and performance-based work culture, where each department has clear and measurable objectives. However, there were some challenges at the initial stage, such as resistance from some employees and a lack of understanding of performance indicators. Nevertheless, factors supporting the success of BSC implementation include strong leadership commitment, routine training, and a participatory evaluation forum, which allows all parties to be involved in the evaluation and improvement process. This study provides important implications for healthcare institutions, particularly clinics, to adopt the BSC as a strategic framework that aligns the organization's vision with measurable and sustainable work practices. Effective BSC implementation is expected to enhance healthcare service quality, making it more efficient and responsive to patient needs.